Effectiveness of a 3 + 0 pneumococcal conjugate vaccine schedule against invasive pneumococcal disease among a birth cohort of 1.4 million children in Australia - Gidding, H.; McCallum, L.; Fathima, P.; Moore, H.; Snelling, Thomas; Blyth, C.; Jayasinghe, S.; Giele, C.; de Klerk, N.; Andrews, R.; McIntyre, P. (Elsevier, 2018)
Background: Most studies use indirect cohort or case-control methods to estimate vaccine effectiveness (VE) of 7- and 13-valent pneumococcal conjugate vaccines (PCV7 and PCV13) against invasive pneumococcal disease (IPD). Neither method can measure the benefit vaccinationprograms afford the unvaccinated and many studies were unable to estimate dose-specific VE. We linked Australia’s national immunisation register with health data from two states to calculate IPD incidence by vaccination status and VE for a 3 + 0 PCV schedule (doses at 2, 4, 6 months, no booster) among a cohort of 1.4 million births. Methods: Births records for 2001–2012 were probabilistically linked to IPD notifications, hospitalisations, deaths, and vaccination history (available until December 2013). IPD rates in vaccinated and unvaccinated children <2 years old were compared using Cox proportional hazards models (adjusting for potential confounders), with VE = (1 − adjusted hazard ratio) × 100. Separate models were performed for all-cause, PCV7, PCV13 and PCV13-non-PCV7 serotype-specific IPD, and for Aboriginal and non-Aboriginal children. Results: Following introduction of universal PCV7 in 2005, rates of PCV7 serotype and all-cause IPD in unvaccinated children declined 89.5% and 61.4%, respectively, to be similar to rates in vaccinated children. Among non-Aboriginal children, VEs for 3 doses were 94.2% (95%CI: 81.9–98.1) for PCV7 serotype-specific IPD, 85.6% (95%CI: 60.5–94.8) for PCV13-non-PCV7 serotype-specific IPD and 80.1% (95%CI: 59.4–90.3) for all-cause IPD. There were no statistically significant differences between the VEs for 3 doses and for 1 or 2 doses against PCV13 and PCV13-non-PCV7 serotype-specific IPD, or between Aboriginal and non-Aboriginal children. Conclusion: Our population-based cohort study demonstrates that >90% coverage in the first year of a universal 3 + 0 PCV program provided high population-level protection, predominantly attributable to strong herd effects. The size of the cohort enabled calculation of robust dose-specific VE estimates for important population sub-groups relevant to vaccination policies internationally.